2015
DOI: 10.1088/0953-4075/48/5/055003
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Autler–Townes splitting to electromagnetically induced transparency based on the dynamics of decaying dressed states

Abstract: The threshold for the transition between Autler–Townes splitting (ATS) and electromagnetically induced transparency (EIT) is studied through examining the dynamics of decaying dressed states, which are derived from the effective Hamiltonian. It is found that the threshold corresponds to the suppression of the Rabi oscillation of the populations by the relaxation as the coupling field becomes weak. Moreover, ATS and EIT belong to two different regimes, the former being in the non-perturbation regime, where ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…Our investigation adds a fresh applications-based perspective to the ongoing discussion centered on phenomenon-based comparisons between EIT and ATS [4,5,[7][8][9][10][11]. Further, it clarifies any potential confusion that may arise between the two perceivably similar EIT and ATS memory protocols, which is important because by understanding the underlying mechanisms of these memories, a proper approach to optimization can be taken: one that yields the best results for a given set of technical and design limitations.…”
Section: Discussionmentioning
confidence: 86%
“…Our investigation adds a fresh applications-based perspective to the ongoing discussion centered on phenomenon-based comparisons between EIT and ATS [4,5,[7][8][9][10][11]. Further, it clarifies any potential confusion that may arise between the two perceivably similar EIT and ATS memory protocols, which is important because by understanding the underlying mechanisms of these memories, a proper approach to optimization can be taken: one that yields the best results for a given set of technical and design limitations.…”
Section: Discussionmentioning
confidence: 86%
“…EIT and ATS have been extensively investigated experimentally and theoretically in lambda (Λ), V and ladder (Ξ, also named cascade in some papers) configuration of three-level systems [5][6][7][8][9][10][11][12][13]. Because EIT and ATS look phenomenologically similar, in recent years many papers focused on the transition between the two regimes [5,[14][15][16][17][18][19][20]. It has been shown that EIT can be observed only in Λ and Ξ configurations for cold systems and in V configuration for hot molecules in the weak coupling a e-mail: doinitabejan@yahoo.com field regime [11][12][13], while ATS may be observed in all configurations in the strong coupling field regime [21].…”
Section: Introductionmentioning
confidence: 99%
“…Anisimov et al [10] also propose an objective method based on Akaike's information criterion (AIC), to discern ATS from EIT in experimental data of a Λtype three-level atom. Recently, a series of experiments [11][12][13] has been performed in which the AIC has been used to discriminate EIT from ATS in Λ-type three-level systems free of Doppler effects. Zhang et al [14] provided a theoretical model using a five-level system and investigated EIT and ATS based on the AIC.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous efforts have already dealt with discriminating EIT from ATS [9][10][11][12][13][14], as reported in the above overview, many of these earlier works are limited to Λ-type systems, deal with Doppler-effect-free coldatom systems or all-optical equivalents of those, assume that the probe is in the weak-field limit, assume that the system is in steady-state, assume a vanishing laser linewidth, and/or assume that there is no interaction between the atoms (or their analogs) that exhibit EIT or ATS. In the present work we explore the EIT/ATS transition in a case where none of these ideal conditions are necessarily satisfied.…”
Section: Introductionmentioning
confidence: 99%